Sri Lanka : Use of Fund Resources-Request for Emergency Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper evaluates Sri Lanka's Request for Emergency Assistance. The Sri Lankan authorities have requested a purchase in an amount of SDR 103.35 million under the IMF's policy for emergency assistance related to natural disasters. In line with IMF policy for Poverty Reduction and Growth Facility (PRGF)-eligible countries, they have also requested the provision of subsidies to reduce the rate of charge to concessional terms. Reconstruction and rehabilitation will support growth momentum in 2005.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet